Rachel: The Union Catalog of the European Network of Judaica and Hebraica Libraries - Musnik, Noémie (Judaica Librarianship, 2014)
The union catalog Rachel was launched in 2004 by four Parisian private libraries with significant holdings in Judaica and Hebraica. Further developed by the Réseau Européen des Bibliothèques Judaica et Hebraica (REBJH; European Network of Judaica and Hebraica Libraries), Rachel moves forward the network’s mission to promote the preservation and increase the use of the recorded heritage of the Jewish people in Europe and around the world. The article reviews the history of the REBJH and its founding members, analyses cataloging practices of member institutions of Rachel, and describes user services provided by this union catalog.